1994
DOI: 10.1073/pnas.91.13.5838
|View full text |Cite
|
Sign up to set email alerts
|

Specific human granulocyte-macrophage colony-stimulating factor antagonists.

Abstract: Human granulocyte-macrophage colonystimulating factor (GM-CSF) is a pleiotropic hemopoietic growth factor and activator of mature myeloid cell function. We have previously shown that residue 21 in the first helix of GM-CSF plays a critical role in both biological activity and high-affinity receptor binding. We have now generated analogues of GM-CSF mutated at residue 21, expressed them in Escherichia coli, and examined them for binding, agonistic, and antagonistic activitles. Binding experiments showed that GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 44 publications
7
89
1
Order By: Relevance
“…3,4 E21R has a dual mechanism of action: antagonism of GM-CSF function, via selective binding to the receptor alpha chain, and induction of apoptosis in cells carrying the GM-CSF receptor. In vitro, E21R inhibits GM-CSF activity on myeloid leukemic cells 5 and in vivo, E21R exerts an antileukemic action in a transplanted animal model, 6 prompting us to consider its potential utility in JMML.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 E21R has a dual mechanism of action: antagonism of GM-CSF function, via selective binding to the receptor alpha chain, and induction of apoptosis in cells carrying the GM-CSF receptor. In vitro, E21R inhibits GM-CSF activity on myeloid leukemic cells 5 and in vivo, E21R exerts an antileukemic action in a transplanted animal model, 6 prompting us to consider its potential utility in JMML.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to speculate on the role of the ␤-subunit (␤ c ) in slowing the dissociation of GM-CSF from the heterodimeric receptor. Studies of GM-CSF mutants support a key role for Glu-21 in binding to the high affinity but not the low affinity receptor (8,(27)(28)(29)(30)(31). These authors would argue for direct binding of the GM-CSF A-helix, centered on residue Glu-21, to the ␤ c .…”
Section: Binding Kinetics Of Sgm-csfr␣-fcmentioning
confidence: 99%
“…Of the seven solventexposed residues in helix A, only Glu 21 was found to play a critical role in binding to the GM-CSF receptor (35,36). Mutagenesis results for solvent-exposed residues in helix D of GM-CSF (36) demonstrated that only Glu 108 and Asp 112 showed significant sensitivity to substitution.…”
mentioning
confidence: 99%